The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ange.202004413
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐Sensitized Activated Photoreaction between Cyanines and Oxime Esters: Free‐Radical Photopolymerization

Abstract: Cyanines comprising either a benzo[e]‐ or benzo[c,d]indolium core facilitate initiation of radical photopolymerization combined with high power NIR‐LED prototypes emitting at 805 nm, 860 nm, or 870 nm, while different oxime esters function as radical coinitiators. Radical photopolymerization followed an initiation mechanism based on the participation of excited states, requiring additional thermal energy to overcome an existing intrinsic activation barrier. Heat released by nonradiative deactivation of the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Preliminary studies indicated the possibility to overcome internal activation barrier of systems comprising 3 b and 3 c in combination with the cation of 5 [16, 38] and a high‐intensity NIR‐LED. Structures 1 , 2 , 3 a , and 4 appear new in this application field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary studies indicated the possibility to overcome internal activation barrier of systems comprising 3 b and 3 c in combination with the cation of 5 [16, 38] and a high‐intensity NIR‐LED. Structures 1 , 2 , 3 a , and 4 appear new in this application field.…”
Section: Resultsmentioning
confidence: 99%
“…However, this differs in the case of a real‐time FTIR setup where heat formed in the reaction does not efficiently leave the system, rather resulting in conditions that reside between an adiabatic and isothermal system in the time frame of the reaction. This has often facilitated NIR‐sensitized radical photopolymerization needing both photons and heat to proceed PET according to an activated scheme [5, 16, 37, 38] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with a limited number of NIR PIs, lanthanide‐doped upconversion materials (UCms) in UCAP can convert NIR light into ultraviolet‐visible light as internally secondary light source to induce available PIs initiating photopolymerization [2b,3] . Since there is unnecessary to design and synthesize extra initiators, UCAP possesses excellent versatility and effectiveness in deep photopolymerization, living/controlled radical polymerization, chiral macromolecules synthesis, biomedical materials and 3D printing [1e,4] . However, the complicated and vague photoinitiation process of UCAP results in the absence of evaluations, which makes it incapable to accurately select or quickly develop an optimal photoinitiation systems to absorb the adequate amount of photons for polymerization.…”
Section: Methodsmentioning
confidence: 99%
“…Oxime esters are efficient photoinitiators because the N-O bond of the structure can be used to generate free radicals quickly and efficiently upon light exposure [ 28 , 29 , 30 ]. Oxime esters with long wavelength absorption have attracted general interest [ 20 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%